Analysis of the implementation of an innovative IT solution to improve waiting times, communication with primary care and efficiency in Rheumatology - José María Pego-Reigosa; Carlos Peña-Gil; David Rodríguez-Lorenzo; Irene Altabás-González; Naír Pérez-Gómez; John Henry Guzmán-Castro; Rodrigo Varela-Gestoso; Reyes Díaz-Lambarri; Alberto González-C; Olga Míguez-Senra; Julia Bóveda-Fontán; Ángeles Charle-Crespo; et al. (BMC, 2022)
Abstract Objective To describe in detail an innovative program based on telemedicine for semi-automated prioritization of referrals from Primary Care (PC) to Rheumatology, for reproducibility purposes, and to present the results of the implementation study. Methods The context and situation were carefully analyzed, paying attention to all processes in place, referral numbers, waiting times, and number of complementary tests prior to discharge from Rheumatology. The composition of the team, aims, users, scope, and implementation phases were defined. Eight process indicators were established and measured before and 32 months after the program implementation. Results The program, which includes IT circuits, algorithms based on response to specific guideline-based checklists, e-consultation, and appointments based on priority, was fully implemented in our health area after a pilot study in two PC centers. After implementation, 6185 rheumatology referrals showed an e-consultation response delay of 8.95 days, and to first face-to-face visit (after e-consultation) of 12.6 (previous delay before program implementation was 83.1 days). Resolution by e-consultation reached 20% (1195 patients did not need seeing the rheumatologist to have the problem solved), and 1369 patients (32%) were discharged after the first visit. The overall resolution rate was 44.0% (2564 discharges/5830 e-consultations). From a random sample of 100 visits, only 10% of patients needed additional complementary tests to make a diagnosis and decision by Rheumatology (20.9% decrease from previous period). Conclusion A careful analysis of the situation and processes, with implementation of simple IT circuits, allows for the improvement of the efficiency and resolution of problems in Rheumatology.